Local and Scientific Knowledge Dialogue in Rice Farming Practice in Aceh Besar District - ulfa, kamalia; Muljono, Pudji; Seminar, Annisa Utami (International Journal of Social Service and Research, 2023)
As government partners, it is appropriate that Keujruen blang and agricultural extension workers as facilitators of the government in the agricultural sector must have the same meaning in agricultural practice activities. It aims to achieve the mission of national development embodied into food security priorities through sustainable agricultural agitation. Collaboration between extension workers and customary institutions can create effective agricultural practices to increase the income and standard of living of farming communities. The focus of this study is to analyze the meaning of agricultural practices owned by extension workers and customary institutions in Sukamakmur Aceh Besar sub-district by understanding the role of each actor. To analyze the meaning of agricultural practices for extension workers and customary institutions, this study uses the concept of hierarchy of meaning contained in the theory of Coordinated Management of Meaning (CMM). This research is presented with qualitative methods with ethnographic design. The place of research was conducted in Sukamakmur District, Aceh Besar. This research was conducted from March to September 2023 through several stages. The determination of informants is done purposively. The analysis used is Ethnograpic Content Ananlysis (ECA). Validity in this study was carried out using data triangulation. The results of the study explained that coordinating the meaning of agricultural practices between extension workers and traditional keujruen blang institutions can be assessed from the role of each actor. The coordination of the meaning of agricultural practices between keujruen blang and extension workers with CMM theory shows the similarity of the meaning of agricultural practices by extension workers and keujruen blang, namely realizing sustainable agriculture through the roles of each actor. The role of keujruen blang to realize sustainable agriculture is by maintaining customs in rice field activities, while the role of extension workers to realize sustainable agriculture is by focusing on organic farming.